Pemilu, Politik Patronase dan Ideologi Parpol - S. L. Harjanto (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2012)
Patronase politic still present in 2014 election process. By its varians, patronase politic is used by legislator candidate and political party in order to win the election in Jakarta. Ironically, these patronase practice is not associated with the ideology of party. These practice get into both the nationalist and Islamist parties not only clearly but also silently. It was closely no differences in the aspect of the form of those patronase. The differences are in the aspect of the actor and target of the patronase